THE MAIN CONGENITAL PATHOLOGY OF THE MUSCULOSKELETAL SYSTEM IN NEWBORNS AND IN INFANTS - V.V. Gorelik; O.M. Gorbatyuk (Bukovynian State Medical University, 2019)
The purpose of this study is the analysis of the morbidity of the musculoskeletal system in newborns and infants during 2010-2013 based on own research data. The most important role in detection of this pathology timely plays the level of knowledge of its clinical peculiarities. It was ascertained that the most widespread orthopedic pathologies in newborns and in infants are such congenital pathology as dysplasia of the hip joint (50,94%), torticollis (27,83%) and clubfoot (15,57%).